STRATEGI PENERAPAN DIGITALISASI DALAM LAPORAN KEUANGAN UNTUK MENINGKATKAN DAYA SAING UMKM DI ERA INDUSTRI 4.0 - Fahmi, Muhammad; Aswat, Ibnu (AKRUAL : Jurnal Akuntansi dan Keuangan, 2024)
This study aims to identify the current conditions, challenges, benefits, and obstacles in the implementation of digitalization of financial reports for MSMEs in Indonesia, as well as to formulate effective strategies and the role of the government in supporting the process. The research method used is qualitative with a phenomenological approach. The study focused on MSMEs in Pontianak City as the object of study. The results of the study indicate that although digitalization of financial reports offers significant benefits such as increased efficiency, accuracy, and accessibility of real-time financial data, MSMEs still face various obstacles. The main challenges include limited technological infrastructure, lack of digital literacy, limited capital for investment in technology, and resistance to changing from traditional to digital methods. Effective strategies include providing training and technical assistance, developing adequate digital infrastructure, and easy access to affordable accounting software. This study also highlights the important role of the government and related stakeholders in supporting the digitalization of MSMEs through policies, regulations, and funding programs.